Ludic-Narrative Strategies for Emotionally Meaningful Literacy in Vulnerable - Martínez Ortega, Jesús Francis (2025)
This qualitative study, framed within an Action-Research design, examined the impact of playful-narrative strategies on the literacy development of 28 second-grade students in a marginalized urban school in Mérida, Yucatán. The intervention —including syllabic bingo games, family storytelling workshops, and culturally embedded narratives— fostered not only technical progress (from 22% to 47% in alphabetic writing level) but also emotional transformations: 82% of participants associated writing with positive emotions, and 64% expressed a sense of self-efficacy in their learning journals. Paradigmatic cases, such as a girl with deaf-mute parents, illustrated writing as a bridge across sensory and emotional worlds. Nevertheless, 21% of students remained in early stages, presumably due to structural barriers like limited parental engagement (45%). The findings suggest that literacy in contexts of precarity is not merely a pedagogical task but a symbolic form of social redress that demands inclusive, context-sensitive teaching approaches.